Release a novel - Ness, Patrick 1971- (Harper Teen, an imprint of HarperCollins Publishers, 2017)
Inspired by Judy Blumes Forever and Virginia Woolfs Mrs. Dalloway, this novel by award-winning author Patrick Ness is a new classic about teenage relationships, self-acceptanceand what happens when the walls we build start coming down. Adam Thorn doesnt know it yet, but today will change his life